Physiopathological Relevance of D-Serine in the Mammalian Cochlea - Wang, Jing; Serratrice, Nicolas; Lee, Cindy J.; François, Florence; Sweedler, Jonathan V.; Puel, Jean-Luc; Mothet, Jean-Pierre; Ruel, Jérôme (Frontiers in Cellular Neuroscience, 2021)
NMDA receptors (NMDARs) populate the complex between inner hair cell (IHC) and spiral ganglion neurones (SGNs) in the developing and mature cochlea. However, in the mature cochlea, activation of NMDARs is thought to mainly occur under pathological conditions such as excitotoxicity. Ototoxic drugs such as aspirin enable cochlear arachidonic-acid-sensitive NMDAR responses, and induced chronic tinnitus was blocked by local application of NMDAR antagonists into the cochlear fluids. We largely ignore if other modulators are also engaged. In the brain, D-serine is the primary physiological co-agonist of synaptic NMDARs. Whether D-serine plays a role in the cochlea had remained unexplored. We now reveal the presence of D-serine and its metabolic enzymes prior to, and at hearing onset, in the sensory and non-neuronal cells of the cochlea of several vertebrate species. In vivo intracochlear perfusion of D-serine in guinea pigs reduces sound-evoked activity of auditory nerve fibres without affecting the receptor potentials, suggesting that D-serine acts specifically on the postsynaptic auditory neurones without altering the functional state of IHC or of the stria vascularis. Indeed, we demonstrate in vitro that agonist-induced activation of NMDARs produces robust calcium responses in rat SGN somata only in the presence of D-serine, but not of glycine. Surprisingly, genetic deletion in mice of serine racemase (SR), the enzyme that catalyses D-serine, does not affect hearing function, but offers protection against noise-induced permanent hearing loss as measured 3 months after exposure. However, the mechanisms of activation of NMDA receptors in newborn rats may be different from those in adult guinea pigs. Taken together, these results demonstrate for the first time that the neuro-messenger D-serine has a pivotal role in the cochlea by promoting the activation of silent cochlear NMDAR in pathological situations. Thus, D-serine and its signalling pathway may represent a new druggable target for treating sensorineural hearing disorders (i.e., hearing loss, tinnitus …).